THE IMPLEMENTATION CHALLENGES OF CHARACTER EDUCATION IN PRIMARY SCHOOLS - Adit Yuliani; Bunyamin Maftuh; Sapriya; Atep Sujana; Rahma Hayati (Jurnal Cakrawala Pendas, 2024)
Character education is the most important factor in shaping good character, especially in primary schools, which can include character values, manners, attitudes, and morals so that students can distinguish good and bad behaviour. Formal education is currently only focused on developing cognitive aspects so the affective aspects of students have not been applied thoroughly in schools. This study aims to analyse the challenges of implementing character education in primary schools. The method used was a systematic literature review (SLR), collecting articles related to problems and solutions in character education in primary schools. Data collected from as many as 181 articles and filtered and obtained into 10 articles through sinta accredited journals. Articles in this study were traced through the Google Scholar database from 2018-2023. Based on the research some students still have problems with poor character such as dishonesty during tests, not being disciplined to follow the rules at school, and not being independent in doing assignments. The implementation of character education must be instilled since elementary school and done well through the example of a teacher and routinely carried out by the school so that students can get used to actions that will become commendable characters that will have an effect in the future. Character cultivation can also be carried out by teachers by slipping character values through the integration of subjects to be taught.